Prospects of exogenous inositols in maintaining of skin, hair and nails condition: A review - Olga A. Gromova; Ivan Yu. Torshin; Nana K. Tetruashvili (IP Berlin A.V., 2022)
Myoinositol (MI) and D-chiroinositol (DCI), used in the therapy of menstrual disorders, polycystic ovarian syndrome (PCOS), hirsutism, acne, gestational diabetes, and other diseases, are required for intracellular signal transduction from insulin and other hormone receptors. Clinical practice shows that, for instance, MI and DCI in the treatment of PCOS improve the condition of skin, hair, and nails. These effects of MI and DCI are related to the normalization of insulin signaling and support of differentiation and growth of various skin cell types (keratinocytes, fibroblasts, epitheliocytes, etc.). The effects of MI and DCI on the skin and its appendages, including in wound healing, can be enhanced by manganese, which provides an antioxidant effect and improves the connective tissue matrix of the skin, and folic acid, which is involved in amino acid metabolism, proliferation, and differentiation of dividing cells.